Coke formation and performance of an intermediate-temperature solid oxide fuel cell operating on dimethyl ether fuel - Su, C.; Ran, R.; Wang, W.; Shao, Zongping (2011)
Dimethyl ether (DME) as a fuel of SOFCs is investigated with great attention paid to coke formation over the Ni-YSZ anode. DME is easily decomposed to CH4, CO and H2 at temperatures above 700 °C, with total conversion occurring at 850 °C over the Ni-YSZ catalyst. These data suggest that the DME electro-oxidation likely proceeds via an indirect pathway. O2-TPO analysis, laser Raman spectroscopy and SEM-EDX characterizations demonstrate coke formation over Ni-YSZ, which is obvious and become more prevalent at higher temperatures. The introduction of CO2 in the fuel gas decreases the CH4 selectivity and effectively suppresses coke formation above 700 °C. The suppression effect is increasingly apparent at higher temperatures. At 850 °C, the anode still maintains geometric integrity after exposure to DME-CO2 (1:1, volume ratio) under OCV condition. With DME or DME-CO2, the fuel cell power output is comparable to results obtained by operating with 3% water humidified hydrogen. No obvious cell degradation from the anode is observed when operating with DME-CO2, while it is obvious with DME. The introduction of CO2 may be a good choice to suppress the coke formation when operating on DME; however, the proper selection of operation temperature is of significant importance. © 2010 Elsevier B.V.